Does Auctioning of Entry Licenses affect Consumer Prices? An Experimental Study - Theo Offerman; Jan Potters (Tinbergen Institute, 2000)
On an increasing scale auctions are used to allocate the licenses tooperate on markets which are thought notsuited for free entry. According to standard economic arguments, thelicense fees paid at the auction will notaffect consumer prices since they constitute a sunk cost. Thisstandard view is not uncontested though. In thepresent paper we experimentally investigate two arguments for apotential upward effect of auctioning onprices: the incorporation of entry fees in prices due to the use ofmark-up pricing rules, and the tendency ofauctions to select the more collusive firms. Our results indicatethat auctioning increases the probability of highprices, and that this is mainly due to the use of mark-up pricingrules.
Keywords: 330; Auktionstheorie; Konzession; Preismanagement; Test; Theorie